Performance of the Abernosa ranch in the production of Ethiopian Boran X Holstein Crossbreed dairy Heifers in Ethiopia - Dekeba, A.; Ayalew, W.; Hedge, P.B.; Tadesse, Z. (2006)
The present study was conducted to evaluate reproductive performance of Ethiopian Boran cows at Abernosa ranch in the production of Boron x Holstein-Friesian Ft crossbred dairy heifers for distribution to smallholder farmers. Performance data from the ranch between 1993 and 2001 was used for this study. The results show delayed age at first conception (53.9 months) and long'calving interval (534.3 days), with average breeding efficiency of 44.6%, average calving rate of 72% and heifer production efficiency of only 38%. The pre and post weaning calf mortality rates were 17.3 and 2.9%, respectively. These led to a very low average cost recovery on in calf heifer production of only 14.6%. Based on the average herd productivity parameters determined in this study, it was calculated that this rate of cost recovery could be improved three fold to 42.8% by introducing such realistic management interventions as replacement of old and unproductive cows with average performing ones, enforcing a clearly defined breeding practice, managing open cows and heifers separately for better beat detection, supplementary feeding and timely mating, and full utilization of the available resources for the key output of the ranch - in-calf crossbred heifers. Furthermore, between 1994 and 2000, annually on average 20% of the crossbred heifers were culled for health difficulties, physical injury and unknown reasons. If this rather high culling rate could be reduced by half through separate and proper management of heifers, the number of available heifers for mating could be increased by 15.4%, and with this, also the number of in calf heifers available for distribution. Overall, it was noted that the production of in calf crossbred heifers in the ranch has been very inefficient. It was therefore recommended that alternative ways of producing crossbred heifers such as contract production with smallholder farmers or commercial farmers and direct production of crossbred heifers in the hands of smallholder farmers who own suitable indigenous cows should be considered for more economical production of crossbred heifers.